Pregnancy Exercise Reduce Oxidative Damage in Pregnant Women - Freddy W. Wagey (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To determine the effect of exercise during pregnancy in reducing oxidative damage marked by decrease of malondialdehyde (MDA) and 8-hydroxy-2-deoxy-guanosine (8-OHdG) levels. Method: A number of 66 pregnant women were recruited in this study and grouped to two groups, i.e. 30 of them as control group and the rest as treatment group. Pregnancy exercise was performed to all 36 pregnant women from 20 weeks gestation on treatment group. The exercise was performed in the morning for about 30 minutes, twice a week until fullterm. Blood sample was taken for MDA and 8 OHdG level at the beginning of research, at 20 weeks of gestation, and at intial delivery or fullterm. Student’s t-test was applied to compared the difference between treatment and control group with 5% significant value. Result: This study reveals that there were significant decrease of MDA and 8-OHdG level amongs treatment and control groups (p < 0.05). Conclusion: Light exercise started from pregnancy age 20 weeks will decrease MDA and raised 8-OHdG levels compared to control group without exercise. [Indones J Obstet Gynecol 2011; 35-2: 57-60] Keywords: oxidative stress, malondialdehyde, 8-hidroxy-2- deoxy-guanosine